Effects of personal factors on lifting patterns - Ho, Kin Ming. (2013)
Low back pain (LBP) is a serious musculoskeletal disorder, with age and gender always being studied as being a factor for causing it, but more often than not, these two factors are studied separately. The objective in this study is to find the correlation of age and gender effects on lifting biomechanics and patterns. Twelve young adults of seven males and five females, and twelve old adults of the corresponding number of males and females were recruited to perform lifting tasks. All participants were required to lift 3 differently weighted boxes (5%, 15% and 25% of their maximum lifting capacity (MLC)), to 3 different levels (wrist height, elbow height and shoulder height), in 2 directions (symmetric and asymmetric). The results showed age having a significant effect on 5 trunk kinematics, 7 knee kinematics and 5 L5/S1 joint kinetics. Gender was also shown to have significant effect on 2 trunk kinematics, 3 knee kinematics and 7 L5/S1 joint kinetics. From the results, young adults tend to have higher kinematics and lower kinetics than old adults and males tend to have higher spinal loads. Collectively, the results indicated the importance of gender and age effects during lifting tasks, but no impact on lifting patterns. Recommendations on workplace design were also made from the results.